Identification of resistance-modifying agents from Pteris vittata L. By untargeted metabolomic analysis and in silico screening - Phuong Nhung, Nguyen; Yen Vy, Dao; Thao Ngan, Nguyen Thi; Kieu Oanh, Nguyen Thi (Academia Journal of Biology, 2025)
Antibiotic resistance is becoming an urgent public health concern worldwide, which leads to the urgent need for research and development of new antibacterials or new resistance-modifying agents. Pteris vittata L., which belongs to the Pteridaceae family, is a hyperaccumulator plant growing in metalliferous soils. This harsh environment is supposed to induce the expression or the dispersion of multidrug-resistant phenotypes through the action of efflux pumps in bacterial membranes to exclude heavy metals. Previous studies showed the potential inhibition of P. vittata extracts on Stenophomonas maltophilia isolates. Therefore, to identify the active compounds in the plant, the whole metabolome of P. vittata was screened by untargeted analysis using the LC-MS-qToF system and then applied virtual docking to investigate the interaction of these compounds on an efflux pump model. Over one hundred compounds extracted from the root and leaf samples were docked on the SmeDEF protein using the Autodock Vina 4.2.6 application. As a preliminary result, we suggested nine flavonoid compounds showing the most negative binding energies with the chosen protein for further in vitro experimental confirmation.